FUNDING CELENGAN PADA BPRS SAFIR BENGKULU - Yani, Erma Putri; Arisandy, Yosy (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2018)
The purpose of this study was to determine the effectiveness of the implementation of the funding piggy bank at PT. BPRS Safir Bengkulu and the factors that caused the stall traders to save in the funding piggy bank at PT. BPRS Safir Bengkulu. The research conducted is field research using qualitative methods. The data used in this study are Primary Data obtained through interviews with the Funding Division, Funding Officer, Costumer Service, General Division and Personnel, and Secondary Data obtained from books related to research problems. After the data is obtained then it is analyzed using qualitative descriptive method which is then analyzed deductively. The results of the study found that (1) the implementation of the funding piggy bank at PT. BPRS Safir Bengkulu. After a customer agreement with the BPRS Safir bank, the bank places the piggy bank with the customer, the customer saves the money in the box. After that the bank took the Warung savings, Hajj savings, and Qurban savings. And recorded according to the nominal savings. (2) factors that cause traders to save in the funding piggy bank at PT. BPRS Safir Bengkulu. Because of the friendly service. maintain customer trust, ease in saving, ease of obtaining information about products.